Implementation of the Safety Riding Program in Preventing Traffic Accidents Against Students in Karawang District - Farid, Muhammad Imam (Police Studies Review, 2023)
The National Police of the Republic of Indonesia (Polri) has a duty to maintain public security and order, enforce the law, and provide protection, protection and services to the public based on article 13 of Law No. 2 of 2002 concerning the Indonesian National Police. Refers to the task of maintaining security and public order. The specific responsibilities of the Indonesian National Police to prevent traffic accidents to the public are explained in article 200 paragraph (1) of Law Number 22 Year 2009 concerning Road Traffic and Transportation. The period of 2017-2019 Traffic Accidents (Laka then) in Karawang Regency increased significantly. The dominant factor in Laka is then the human factor, especially in adolescents. In an effort to prevent laka then the students of the police carry out community traffic education activities through the Safety Riding program by the Unit of the Karawang Police Precinct Unit. This study aims to obtain a description of the implementation of the Safety Riding program, the factors that influence the implementation of the Safety Riding program, and the optimization of the implementation of the Safety Riding program by the Unit of the Karawang Regional Police Traffic Unit in order to prevent Laka in the Karawang regency. This study uses a qualitative approach to the type of case study research, data collection methods through observation, interviews and document review. The results of this study are that the Safety Riding Program implemented by the Karawang Police Traffic Police Unit Unit is not optimal, because there are still deficiencies in the managerial implementation of the Safety Riding program, There are factors that support and hinder the implementation of the Safety Riding Program internally and externally. Optimizing the Safety Riding program can based on 6M theory and the concept of Public Relations. Based on the results of research conducted by the author, it is recommended to make a SOP for the Riding Safety program significantly and increase the ability and skills of Dikyasa Unit members related to the implementation of the Safety Riding program so that the socialization given is more felt by the impact on students.